Percutaneous management of severe hemoptysis in a patient after Fontan surgery - Alcalá-Marcos, Katherine (2020)
We present the case of a patient with a history of single ventricle tricuspid atresia, double outlet of the left ventricle and hypoplasia of the pulmonary artery ring. The patient was treated with Glenn's surgery at the age of 7 and at age 16, the patient received fenestrated extracardiac Fontan surgery. After 1 month of Fontan surgery she presented severe hemoptysis without adequate response to medical management. Percutaneous closure of aortopulmonary fistulas with coils was performed, with favorable evolution, without presenting recurrences of hemoptysis.